Evaluation of Plasma Neurofilament Light Chain Levels as a Biomarker of Neuronal Injury in the Active and Chronic Phases of Autoimmune Neurologic Disorders - Kammeyer, Ryan; Mizenko, Christopher; Sillau, Stefan; Richie, Alanna; Owens, Gregory; Nair, Kavita V.; Alvarez, Enrique; Vollmer, Timothy L.; Bennett, Jeffrey L.; Piquet, Amanda L. (Frontiers in Neurology, 2022)
Objective To evaluate plasma neurofilament light (NfL) levels in autoimmune neurologic disorders (AINDs) and autoimmune encephalitis (AE). Background Each particular neural autoantibody syndrome has a different clinical phenotype, making one unifying clinical outcome measure difficult to assess. While this is a heterogeneous group of disorders, the final common pathway is likely CNS damage and inflammation. Defining a biomarker of CNS injury that is easily obtainable through a blood sample and reflects a positive treatment response would be highly advantageous in future therapeutic trials. Measurement of blood concentration of neurofilament light (NfL) chain, however, may provide a biomarker of central nervous system (CNS) injury in AE and other AINDs. Here we provide an initial evaluation of plasma NfL levels in AE as well as other AINDs during active and chronic phases of disease and demonstrate its potential utility as a minimally-invasive biomarker for AE and AINDs. Design/Methods Patients were retrospectively identified who were enrolled in the biorepository at the Rocky Mountain MS Center at the University of Colorado, or were prospectively enrolled after initial presentation. Patients had a well-defined AIND and were followed between 2014 and 2021. NfL was tested using the Single Molecule Array (SIMOA) technology. Patients with headaches but without other significant neurologic disease were included as controls. Results Twenty-six plasma and 14 CSF samples of patients with AINDs, and 20 plasma control samples stored in the biorepository were evaluated. A positive correlation was found between plasma and CSF NfL levels for patients with an AIND (R2 = 0.83, p < 0.001). Elevated plasma levels of NfL were seen in patients with active AE compared to controls [geometric mean (GM) 51.4 vs. 6.4 pg/ml, p = 0.002]. Patients with chronic symptoms (>6 months since new or worsening symptoms) of AE or cerebellar ataxia (CA) showed a trend toward lower plasma NfL levels (GM 15.1 pg/ml) compared to active AE or CA. Six patients with longitudinal, prospective sampling available demonstrated a trend in decreased plasma NfL levels over time. Conclusions Our findings support the use of plasma NfL as a potential minimally-invasive biomarker of CNS injury.